Effect of reaction temperature and time on the physical properties of CTAB-assisted hydrothermally grown ZnO nanostructures. (2022) - Mahajan, Sunil; Jagtap, Shweta
Abstract: This manuscript describes the effect of reaction temperature and time on the structural, morphology and optical properties of cetyltrimethylammonium bromide (CTAB) -assisted ZnO nanostructure grown through hydrothermal process. The samples are characterized by using X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), UV–Vis spectroscopy and Fourier transform infra-red spectroscopy. XRD confirmed the hexagonal phase of ZnO. FESEM images estimated the average particle size of nanoparticles in the range of 20–50 nm. The optical band gap estimated by UV–Vis spectra were depends on reaction temperature and time and are in the range of 3.12 – 3.17 eV. A current–voltage (I–V) characteristic proves that conductivity of ZnO nanoparticles also depends upon hydrothermal reaction conditions.